Internal Control Implementation and Earning Management: A Mediation Effect Testing - Juliana, Anisa Nur; Reskino, Reskino (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
There must be clear evidence about whether internal control mediates earnings management in the relationship between financial distress and tax planning. This research analysed the direct effect of financial distress and tax planning on earnings management and the indirect effect of financial distress and tax planning on earnings management through internal control. A sample of 126 secondary observation data from 21 samples of SOCs companies and non-financial SOCs subsidiaries listed on the Indonesia Stock Exchange for the 2016-2021 period was used. The test results showed that financial distress had a direct impact on internal control and earnings management, while tax planning did not have a direct impact. The study's findings also do not indicate that internal control can mediate the relationship between financial distress and tax planning on earnings management. Further research is needed to add other variables that can, directly and indirectly, affect earnings management.